Effect of heaven worship to the idioms of Chinese and Kazakh languages - Даулет, Ф. Н.; Оразакын, Ф. (Journal of Oriental Studies, 2018)
The article presents idioms of Chinese and Kazakh languages, dating back to Heaven worship. Lexical and semantic analysis allows to draw conclusions about the similarities and the differences between Chinese and Kazakh idioms with the word «sky»